Respiratory and general health complaints in subjects exposed to sandstorm at Riyadh, Saudi Arabia - Ayoub Meo, Sultan (Professional Medical Publicaitons, 2013)
Objective: Sandstorms are metrological events and frequently occur in many regions throughout the world. Sandstorms are a main source of long-distance transport of dust, air pollution and cause various health problems. This study aimed to investigate the acute respiratory and general health complaints in subjects exposed to sandstorm at Riyadh, Saudi Arabia.